MODEL ECONOMIC ORDER QUANTITY (EOQ) DENGAN MEMPERTIMBANGKAN SEBAGIAN PENUNDAAN WAKTU PEMBAYARAN PADA SISTEM PARSIAL BACKORDER - Maslahah, Heny; ., Sunarsih; ., Farikhin (MATEMATIKA, 2016)
The problem of inventories commonly facing the company is determining the optimal order quantities so the demand must be fulfilled. In transaction betwen seller and buyer specified delay of payment is offered by the seller, so given one of alternative the inventory model an Economic Order Quantity (EOQ) with consider partial delayed payment on the partial backordering system. In the inventory model, retailer allowed to make partial payment at the beginning of the period to supplier and the remaining amount can be paid at the end of the period has been determined. There are two condition of stockout are stockout on the condition of lost sales Â and stockout on the condition of backorder . Based on the inventory model can determined when the period to make order and how many should be order, so the total cost of inventory issued to be minimum and total profit can be maximum.Â